KAJIAN MUTU DAN DAYA SIMPAN DENDENG UDANG PUTIH (Penaeus merguensis) SELAMA PENGEMASAN DAN PENYIMPANAN SUHU RUANG - Yulia Delviani; Susi Lestari; Shanti Dwita Lestari; Sherly Ridhowati (AGROINTEK, 2021)
The white shrimp (Penaeus merguensis)is abundant in Indonesia which could be made the jerky product to increase its shelflife. This study was aimed to determine the quality and shelflife of vacuum and non- vacuum  packed white shrimp jerky stored at room temperature. And,  the packed of white shrimp jerky was stored at room temperature for 0, 3, 6 and 9 days. The data obtained were analyzed using paired sample t-test. The condition of packaging had affected the quality and storage times for this jerky. The average water content  value was 23,01% (dry basis,db) for all the treatments. For 9 days, the TVB-N (total volatile based- nitrogen) and TPC (total plate count) were 22,41% mgN/100g and 3,27 log CFU/g (vacuum packed), then 26,52 mgN/100g and 6.12 log CFU/g (non-vacuum packed), respectively. During storage,  total yeast and fungi, as well as  aw (activity water), have increased. The vacuum- packaged white shrimp jerky was the best option for storing this product, and it has a shelflife of up to 9.